Multisensory Development 2012
DOI: 10.1093/acprof:oso/9780199586059.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

The role of intersensory redundancy in early perceptual, cognitive, and social development

Abstract: In the simplest of terms, attention refers to a selectivity of response. Man or animal is continuously responding to some events in the environment and not to others that could be responded to (or noticed) just as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
177
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(197 citation statements)
references
References 111 publications
15
177
0
5
Order By: Relevance
“…Firstly, it is notable that the observed preference for spatial incongruency in six-and ten-month-old infants is broadly consistent with a number of accounts of multisensory development. Bahrick & Lickliter's (2012) intersensory redundancy hypothesis predicts greater preference for spatially congruent displays in young infants, but allows for attention to move more towards incongruent (or non-redundant) multisensory stimuli after the first half year of age. Gergely & Watson's (1999) account of early social-emotional development rests on the idea of a "contingency detection module" which switches from a preference for perfect contingency (which includes spatial congruency; see also Rochat, 1998) up until 3 months of age, to a preference for imperfect contingency (including spatial incongruency) beyond that point.…”
Section: Visual-tactile Co-location In Infants 13mentioning
confidence: 99%
“…Firstly, it is notable that the observed preference for spatial incongruency in six-and ten-month-old infants is broadly consistent with a number of accounts of multisensory development. Bahrick & Lickliter's (2012) intersensory redundancy hypothesis predicts greater preference for spatially congruent displays in young infants, but allows for attention to move more towards incongruent (or non-redundant) multisensory stimuli after the first half year of age. Gergely & Watson's (1999) account of early social-emotional development rests on the idea of a "contingency detection module" which switches from a preference for perfect contingency (which includes spatial congruency; see also Rochat, 1998) up until 3 months of age, to a preference for imperfect contingency (including spatial incongruency) beyond that point.…”
Section: Visual-tactile Co-location In Infants 13mentioning
confidence: 99%
“…Likewise, very young infants detect visualtactile synchrony between brush strokes applied to a viewed body, and strokes applied to their own face (Filipetti, Johnson, Lloyd-Fox, Dragovic & Farroni, 2013) or limbs (Zmyj, Jank, Schütz-Bosbach & Daum, 2011). These sensitivities reflect infants' early abilities to detect common properties of stimuli -in this case, temporal and spatial properties of stimulation across the senses -what has been referred to in the literature as amodal perception (Bahrick & Lickliter, 2012). These abilities are argued to form the developmental building blocks for the identification of self (Bahrick, 2013) and the distinction between self and other.…”
mentioning
confidence: 99%
“…
The Intersensory Redundancy Hypothesis (IRH; , 2012 predicts that early in development information presented to a single sense modality will selectively recruit attention to modality-specific properties of stimulation and facilitate learning of those properties at the expense of amodal properties (unimodal facilitation).Vaillant (2010) demonstrated that bobwhite quail chicks prenatally exposed to a maternal call alone (unimodal stimulation) are able to detect a pitch change, a modality-specific property, in subsequent postnatal testing between the familiarized call and the same call with altered pitch. In contrast, chicks prenatally exposed to a maternal call paired with a temporally synchronous light (redundant audiovisual stimulation) were unable to detect a pitch change.
…”
mentioning
confidence: 99%
“…The Intersensory Redundancy Hypothesis (IRH; , 2012 predicts that early in development information presented to a single sense modality will selectively recruit attention to modality-specific properties of stimulation and facilitate learning of those properties at the expense of amodal properties (unimodal facilitation).…”
mentioning
confidence: 99%
See 1 more Smart Citation